2018
DOI: 10.5194/isprs-archives-xlii-3-w4-363-2018
|View full text |Cite
|
Sign up to set email alerts
|

Applying Random Forest Classification to Map Land Use/Land Cover Using Landsat 8 Oli

Abstract: <p><strong>Abstract.</strong> This study used the Random Forest classifier (RF) running in R environment to map Land use/Land cover (LULC) of Dak Lak province in Vietnam based on the Landsat 8 OLI. The values of two RF parameters of ntree (number of tree) and mtry (the number of variables used to split at each node) were tested and compared. In current study the best results indicate the number of suitable decision trees involved in the classification process is 300 (ntree), and the suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Additionally. These accuracy results are consistent with previous studies of [67][68][69][70]. However, to apply the RF model under the EnMap BOX software, users are required to observe the preliminary LULC result and add more training sample points to increase the accuracy of classification as mentioned by Reference [71].…”
Section: Lulc Assessment Change and Trendsupporting
confidence: 88%
“…Additionally. These accuracy results are consistent with previous studies of [67][68][69][70]. However, to apply the RF model under the EnMap BOX software, users are required to observe the preliminary LULC result and add more training sample points to increase the accuracy of classification as mentioned by Reference [71].…”
Section: Lulc Assessment Change and Trendsupporting
confidence: 88%
“…The optimal parameters were determined based on classification error. For the IMG 2-SVM combination and the IMG 4-SVM combination, the optimal C of 2 3 and Gamma of 0.1 produced classification errors of 0.2283 and 0.1525, respectively, while for the IMG 1-SVM and IMG 3-SVM combinations, the optimal C of 2 5 and 2 6 , both with Gamma of 0.1, produced classification errors of 0.2212 and 0.2145, respectively.…”
Section: Remote Sens 2020 12 X For Peer Review 2 Of 28mentioning
confidence: 97%
“…In the last decade, non-parametric methods including support vector machine (SVM) [35][36][37], k-nearest neighbors (k-NN) [38,39], and random forests (RF) [40][41][42] have gained attention for remote sensing-based land cover classification. However, both SVM and RF require the selection of values for multiple parameters that affect their efficacy, and both are computationally intensive [6,35]. For k-NN, Naidoo et al (2012) [43] reported difficulty in selecting the optimal value of k and that the genetic algorithms recommended for optimization can be computationally intensive [44,45].…”
Section: Classification Techniquesmentioning
confidence: 99%
See 2 more Smart Citations